2021
DOI: 10.52547/jrums.20.2.163
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Ambivalence over Emotional Expression and Health-Related Quality of Life and Adherence to Treatment in Cancer Patients: The Mediating Role of Depression and Social Support: A Descriptive Study

Abstract: Background and Objectives: Ambivalence over emotional expression plays an important role in quality of life and adherence to treatment in cancer patients. The aim of this study was to determine the mediating role of depression and social support in the relationship between ambivalence and quality of life and adherence to treatment in cancer patients. Materials and Methods:The present study was descriptive and based on structural equation modeling. For this purpose, 206 cancer patients referred to Dezful medica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Factor analysis identi ed two main components that together accounted for 65.9% of the variance (43). In the study by Beshiri Nezhadyan et al, the reliability of this questionnaire was also calculated using Cronbach's alpha method, yielding a value of 0.85 (44).…”
Section: Data Collection Toolsmentioning
confidence: 99%
“…Factor analysis identi ed two main components that together accounted for 65.9% of the variance (43). In the study by Beshiri Nezhadyan et al, the reliability of this questionnaire was also calculated using Cronbach's alpha method, yielding a value of 0.85 (44).…”
Section: Data Collection Toolsmentioning
confidence: 99%
“…The suppression of emotion may lead individuals to suffer alone and in silence [28]. In cancer patients, AEE has been associated with higher levels of pain behavior, being overly reserved or non-communicative, having anxiety and depressive symptoms, poor self-effacing behaviors in relationships, poorer emotional well-being, and non-adherence to treatment [29].…”
Section: Emotional Expressionmentioning
confidence: 99%
“…Results of a study by Servaes et al (1999) on inhibited emotional expression in breast cancer patients showed significantly higher levels of AEE, which was a reaction to their disease, not a reflection of personality traits. A growing literature on patients dealing with cancer has since linked AEE in response to disease to higher levels of being reserved, anxiety and depressive symptoms, pain behavior, poor emotional well-being, low levels of energy and general health, and eventually to low adherence to treatment, contributing importantly to understanding cancer patients’ experience of and coping with symptoms of the disease (Bashiri Nejadian et al, 2021; Lu et al, 2015; Porter et al, 2005; Servaes et al, 1999). In turn, childhood maltreatment can be placed among variables that have been associated with specific types of emotion dysregulation, including alterations in the expression of emotions, expressive suppression, or AEE (Kim & Cicchetti, 2010; Weissman et al, 2019).…”
Section: Introductionmentioning
confidence: 99%